Airtel Zero : data pricing, two sided markets led business models and net neutrality - Sahay, Arvind (London : Indian Institute of Management, Ahmedabad, 2015)
It was June 2015 and the Airtel office in New Delhi needed to come to a decision soon. Two months earlier, Shyam Mardikar, Chief of Strategy at Bharti Airtel, had opined that "the Internet, I believe, was neutral, is neutral and will be neutral. There is absolutely no agenda, no direction, no industry force coming in the way." He was speaking at an industry conference in the aftermath of the launch of "Airtel Zero" that adopted a data pricing approach that, many said, violated the principle of net neutrality.
Originally published in Sahay, A. (2015). Airtel Zero: Data pricing, two sided markets led business models and net neutrality. MAR0472. Ahmedabad: Indian Institute of Management, Ahmedabad.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Airtel (Firm); Multi-sided plat form businesses -- India -- New Delhi; Telecommunication -- India -- New Delhi; Service industries -- India -- New Delhi; Markets -- India -- New Delhi; Pricing -- India -- Mathematical models; Network neutrality -- India -- New Delhi